KARAKTERISTIK KEPALA DAERAH DAN AUDIT DELAY LAPORAN KEUANGAN PEMERINTAH DAERAH DI INDONESIA - Frasti, Hesy Erlisa; Dita, Elvanya Purba; Pracinthea, Euodia; Syahputra, Ade; Widyawati, Arini; Hananto, Santoso Tri (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2017)
This study aimed to examine the effects ofÃ‚Â regent/ mayorÃ‚Â characteristics on financial statement of local governmentÃ¢â‚¬â„¢s audit delay in Indonesia. Regional head are characterized by age, educational background, executive work experience, and educational level. The population of this study were all of districts/municipalitie in Indonesia. This study uses 142 districts/municipalities as sample using purposive sampling method. The secondary data was obtained from Audit Board of the Republic of Indonesia (BPK-RI) and Ministry of Home Affairs of the Republic of Indonesia (Kemendagri). Data was analyzed usingÃ‚Â regressionÃ‚Â model.Ã‚Â The analysis showedÃ‚Â thatÃ‚Â theÃ‚Â economicsÃ‚Â orÃ‚Â accounting educational background has negatively affected on financial statement of local governmentÃ¢â‚¬â„¢s audit delay in Indonesia. However, age, executive work experience, and education level do not affect financial statement of local governmentÃ¢â‚¬â„¢s audit delay in Indonesia.